Kristeva, Julia and Sylvere Lotringer (Ed.), (2002), “Revolt She Said” An Interview By Philippe Petit, New York, Semiotext(e), 138p. (2010)
Este documento contiene en texto completo el articulo Kristeva, Julia and Sylvere Lotringer (Ed.), (2002), “Revolt She Said” An Interview By Philippe Petit, New York, Semiotext(e), 138p. publicado en Desafíos; Vol. 13 (2005): (julio-diciembre,0); 267-270;2145-5112;0124-4035